Respuesta :
The transformation starts with T-1, 1(x, y) and ends with RO, 90° (counter-clockwise).
To find the original point, we work backwards.
We start with RO, -90° (clockwise):
[tex](x, y)\rightarrow(y, -x)[/tex]
which gives
[tex](-4, 1)\rightarrow(1, 4)[/tex]
We then do the reverse of T-1, 1(x, y), which is T1, -1(x, y):
[tex](x, y)\rightarrow(x+1, y-1)[/tex]
which gives
[tex](1, 4)\rightarrow(2, 3)[/tex]
so the answer is [tex](2, 3)[/tex].
To find the original point, we work backwards.
We start with RO, -90° (clockwise):
[tex](x, y)\rightarrow(y, -x)[/tex]
which gives
[tex](-4, 1)\rightarrow(1, 4)[/tex]
We then do the reverse of T-1, 1(x, y), which is T1, -1(x, y):
[tex](x, y)\rightarrow(x+1, y-1)[/tex]
which gives
[tex](1, 4)\rightarrow(2, 3)[/tex]
so the answer is [tex](2, 3)[/tex].